THE DEVELOPMENT OF INTERACTIVE E-BOOK ON ECOSYSTEM TOPIC TO TRAIN DIGITAL LITERACY OF 10TH GRADE SENIOR HIGH SCHOOL STUDENTS - Alma Dwi Rahmawati; Herlina Fitrihidajati (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2023)
One of abilities that 2013 Revised Curriculum demands is digital literacy skills. The results of Kominfo survey shows that digital literacy level of East Java high school students is low. One of media that can train digital literacy is an interactive electronic book. Biology learning at SMA Negeri 1 Tarik never use interactive e-books. Therefore, it’s necessary to develop interactive e-book to train students' digital literacy. The aims of this research are 1) to produce a valid interactive e-book on ecosystem topic to train digital literacy, and 2) to describe the practicality of interactive e-book on ecosystem topic to train digital literacy. This research was a development research used the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The parameters assessed include the level of validity based on aspects of presentation, content, and language and the practicality based on the implementation of the e-book, exercises scores, and response student questionnaires. Validity assessed by two material experts and one Biology teacher. The level of practicality of e-book was tested on 20 students of SMA Negeri 1 Tarik. Descriptive quantitative data analysis. The results showed that 1) the level of validity of e-book got 97.50% with very valid interpretation and 2) the level of practicality of e-book in terms of the implementation of the e-book got 97.08% with very well implemented and practical category, based on the exercises scores got 100% Complete with very practical category, and in terms of student response questionnaire got 97.20% with very practical interpretation.